The most influential countries in market orientation: A bibliometric analysis between 1990 and 2016. (1st August 2018) - Valenzuela-Fernández, Leslier; Merigó, José M; Nicolas, Carolina
The purpose of this article is to analyze the most productive and influential countries engaging in market orientation (MO) research between 1990 and 2016. This article shows the general trajectories of these countries, the relationships among them, and their research in the area of MO by analyzing results on citations and publications. The article uses applied bibliometric techniques on available information found in the Web of Science. The results show that the 10 leading countries produce more than 70% of total publications, where the United States leads in all indicators, followed by the United Kingdom and China. Furthermore, although there has been a steady increase in overall number of publications, this trend is not shared evenly among different nations.